PENGARUH PRODUK, HARGA, TEMPAT, DAN PROMOSI TERHADAP LOYALITAS KONSUMEN DENGAN VARIABEL INTERVENING KEPUASAN KONSUMEN PADA CV. KHASANAH SARI BAKERY - Heru Sugianto; Guston Sitorus; Yosi Stefhani (Jurnal Satya Mandiri Manajemen dan Bisnis, 2024)
The aim of this research is to determine the influence of product, price, place and promotion on consumer loyalty as mediated by consumer satisfaction. The independents variables are product, price, place and promotion. The dependent variable is consumer loyalty and the intervening or mediating variable is consumer satisfaction. The research was conducted in October 2023 - January 2024 with total of 100 respondents, using purposive sampling technique. The method used in this research is quantitative, and the data is processed using SPSS 29. The research results show that product, price, place and promotion directly influence consumer satisfaction and consumer loyalty. Then, indirectly, product, price, place and promotion through consumer satisfaction influence consumer loyalty. Keywords: Consumer Loyalty, Consumer Satisfaction, Product, Price, Place and Promotion